Immobilized Crosslinked Pectinase Preparation on Porous ZSM-5 Zeolites as Reusable Biocatalysts for Ultra-Efficient Hydrolysis of β-Glycosidic Bonds - Liu, Can; Zhang, Liming; Tan, Li; Liu, Yueping; Tian, Weiqian; Ma, Lanqing (Frontiers in Chemistry, 2021)
We reported an immobilized enzyme catalyst of pectinase@ZSM-5 by using a simple combined strategy involving the Van der Waals adsorption of pectinase followed by crosslinking of the adsorbed pectinase with glutaraldehyde over porous ZSM-5 zeolites. The as-prepared pectinase@ZSM-5 showed a conformal coating of the pectinase layer over various ZSM-5 supports. The porous pectinase@ZSM-5 presented ultra-efficient biocatalytic activity for hydrolyzing the β-glycosidic bonds in a model substrate of 4-nitrophenyl β-D-glucopyranoside, with a broad operating temperature range, high thermal stability, and excellent reusability. For example, the pectinase@ZSM-5 showed a relative activity nine times higher than that of free pectinase at a high temperature of 70 °C. This was demonstrated by the thermal inactivation kinetic analysis based on the Arrhenius law: pectinase@ZSM-5 showed a higher activation energy for denaturation (315 kJ·mol-1) and a longer half-life (62 min-1) than free pectinase. The Michaelis enzyme kinetic analysis also indicated a higher maximal reaction velocity of pectinase@ZSM-5 (0.22 µmol⋅mg-1⋅min-1). This was attributed to the microstructures of the immobilized pectinase@ZSM-5 which offered a heterogeneous reaction system that decreased the binding affinity between the substrate and pectinase and modulated the kinetic characteristics of the enzyme. Additionally, pectinase@ZSM-5 showed the best ethanol tolerance compared to all of reported pectinase-immobilized catalysts, and also presented a 247% higher activity than free pectinase at a 10% (v/v) ethanol concentration. Furthermore, pectinase@ZSM-5 exhibited the potential in practical engineering applications which promoted the hydrolysis of β-glycosidic bonds in baicalin converting into baicalein, with a 98% conversion rate that is 320% higher than that of free enzyme.